Peningkatan Kemampuan Membaca Permulaan Melalui Metode Struktural Analitik Sintetik - Muriani, Yanie; MS, Zulela; Suseno, Muchlas (AR-RIAYAH : Jurnal Pendidikan Dasar, 2018)
The purpose of this study was to describe the beginning reading skill through Structural Analitic Sintetic Methods in the class I of Elemantary School Ciampea 02 Bogor. The method used is descriptive research type of class action. The subjek of the reseach were teacher and students of 20 people. The technique used is observation. Data collection tool was a teacher and student observation sheets. This research was conducted through a twice cycle, the research procedure using the planning, implementation, observation, and reflection. The results obtained are fluentthe beginning reading skills of students in the first cycle reaches 65%, reaching 85%. The second cycle, it was increased 20%. By using Structural Analitic Sintetic Methods can improve the beginning reading skills of student fluent in Indonesian language learning on the class I of Elementary School Ciampea 02 Bogor.